RESEARCH DIRECTIONS IN MODERN POLITICAL SCIENCE: A REVIEW - Peer Amir Ahmad (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The study offers a comprehensive examination of the evolving landscape of political science scholarship. Its primary objectives are to identify current research themes, assess methodological innovations, explore theoretical developments, and examine interdisciplinary trends within the field. The study highlights that contemporary political science research is characterized by a diverse array of themes, including globalization, environmental politics, populism, and digital governance. It underscores the importance of understanding these themes in the context of current political dynamics. The study evaluates the methodological approaches adopted by researchers, emphasizing both quantitative and qualitative methods, as well as interdisciplinary collaborations. It identifies a growing trend towards methodological pluralism and the integration of insights from various disciplines. The study also recognizes the ongoing theoretical developments in political science, with scholars revisiting established theories and developing new frameworks to address modern political challenges.